Perbandingan Penerapan Metode VBEOQ dan Metode Persediaan Multi Item Periode Pemesanan Tunggal untuk Meningkatkan Economic Value Added (EVA) Pada Usaha Mikro - Triska, Anita; Hadi, Muthia Nurul (Diophantine Journal of Mathematics and Its Applications, 2024)
Every company requires minimum costs in controlling inventory and maximizing the company value. The company value is an investor's perception of the company success level. Therefore, the inventory management system have to contribute to realize these goals. Besides influencing the company value, inventory control is also useful to expedite the company activities. An alternative solution to maximize the company value is by increasing the economic value added (EVA). The change of EVA ΔEVA) can be analyzed using the Value Based Economic Order Quantity (VBEOQ) method which each item is ordered separately. However, in a company may manage many items. In order to overcome this problem, ΔEVA can be analyzed using the multi-item inventory method of a single order period. These two methods are used to analyze EVA in the micro enterprise Depot Tutup Galon X. Based on the analysis, it is found that by using the VBEOQ method and multi item inventory for a single order period increase the ΔEVA as Rp12,629,947,00 and Rp14,355,057,00, respectively. These results indicate that applying the multi-item inventory method for a single order period at Depot Tutup Galon X is better since it increases the ΔEVA larger.